Dynamics of Natural Electric Field as the Indicator for Sites of Landslide Hazard in a Technogenic Landscape (Example of Belarus) - Gusev, A. P.; Kaleychik, P. A.; Fedorsky, M. S.; Shavrin, I. A. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2018)
The results of studying the dynamics of the natural electric field (NEF) in zones with different range of the landslide activity are considered. The study was carried out on the test sites: the banks of the Sozh and Dnieper Rivers, a quarry for the sand extraction. It was established that the amplitude of diurnal variations of the NEF on landslide-active areas is 20-30 mV, with background values (outside the landslide-active section) of 1–8 mV. This effect significantly exceeds the measurement error 1–2 mV.